Characterization of an Enterococcus faecalis bacteriophage SFQ1 as a potential therapeutic agent - Song, Fuqiang; Sheng, Jun; Tan, Jishan; Xie, Huajie; Wang, Xiaoyu; Guo, Wenqiong (Frontiers in Microbiology, 2023)
Enterococcus faecalis is a well-established resident of the human gastrointestinal tract and is also a major cause of human infections. Unfortunately, therapeutic options for E. faecalis infections remain limited, particularly with the emergence of vancomycin-resistant strains in hospital settings. Consequently, there has been a renewed interest in phage therapy as an alternative to antibiotics. In this study, we have isolated a bacteriophage, vB_EfaS-SFQ1, from hospital sewage, which effectively infects E. faecalis strain EFS01. Phage SFQ1 is a siphovirus and exhibits a relatively broad host range. Furthermore, it has a short latent period of approximately 10 min and a large burst size of about 110 PFU/cell at a multiplicity of infection (MOI) of 0.01, and it could effectively disrupt the biofilms formed by E. faecalis. Thus, this study provides a detailed characterization of E. faecalis phage SFQ1, which has great potential for treating E. faecalis infections.